Rotavirus infection: An unrecognised disease in Nepal - Pun, SB (Kathmandu University Medical Journal, 2010)
Rotavirus is the most common cause of acute infectious gastroenteritis in young children and is associated with substantial morbidity and mortality worldwide, mostly in developing countries. The global rotavirus disease burden has prompted study on their basic research, molecular epidemiology and vaccine development. Little is known about rotavirus infection among health professionals in Nepal. This article summarises basic and clinical features, treatment and prevention, epidemiological pattern, challenges and recommendations of human rotavirus infections in Nepal. Key words: Rotavirus; Epidemiology; Challenges and Recommendations; Nepal DOI: 10.3126/kumj.v8i1.3236 Kathmandu University Medical Journal (2010), Vol. 8, No. 1, Issue 29, 135-140